A Novel Heuristic Based Task Scheduling Algorithm to Minimize the Makespan in Cloud Environment - O.S. Abdul Qadir, Dr. G. Ravi (International Journal of Advanced Science and Technology, 2020)
Cloud computing is a network of resources and services to store and process data. It provides the delivery of computing services over the Internet. The task scheduling algorithm maps the tasks with available resources. In cloud scheduling Makespan and resource utilization are two important factors to consider. An efficient task scheduling algorithm produces a near to optimal assignment of tasks to the resources. This reduces the makespan. Task scheduling algorithms are heuristic in nature. A heuristic algorithm produces a good solution in a fast time. In this paper a novel heuristic-based task scheduling [NHBTS] algorithm has been designed to minimize the makespan. The [NHBTS] algorithm uses the coefficient of variance to determine the efficiency of scheduling. The NHBTS algorithm is compared with six standard heuristic scheduling algorithms on three different problem sets consisting of low, medium and high tasks and resources. The experimental results clearly indicate that the NHBTS methodology outperforms the standard task scheduling algorithms. Keywords: Cloud Computing, Task Scheduling, Scheduling algorithms, ETC Matrix, Makespan.